Formulasi dan Uji Iritasi Gel Antibakteri Dari Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa bilimbi Linn) Terhadap Bakteri Staphylococcus aureus dan Pseudomonas aeruginosa [Formulation and Irritation Test of Antibacterial Gel from Star Furit Leaves (Averrhoa bilimbi Linn.) Ethanol Extract Againts Bacteria Staphylococcus aureus and Pseudomonas aeruginosa] - Sutriningsih Sutriningsih; Zuraida Sagala; Marhamah Marhamah (Universitas Pelita Harapan, 2018)
Starfruit (Averrhoa bilimbi Linn.) is containing several chemical contents including tannins, alkaloids, flavonoids, polyphenols and saponins, which can be efficacious as an antibacterial. The purpose of this study is determine stability of gel and the effect of gel formulation ethanol extracted from leaves starfruit (Averrhoa bilimbi Linn.) against the antibacterial activity of Staphylococcus aureus and Pseudomonas aeruginosa. This is an experimental laboratory research where the formulation of ethanol extracted from the leaves of starfruit (Averrhoa bilimbi Linn.) which obtained from the process of maceration with 96% of ethanol solvent formulated in a gel dosage form. Gel formulations of the ethanol extracted from leaves starfruit was made with various concentration of the extract including 35%, 50% and 65% with hidroksi propil metil cellulose ( HPMC) as the base. We used without-extract as the negative control and 0.1% of gentamicin ointment as the positive control. The result gel from antibacterial activity was then processed using the agar diffusion method .The use of a gel formulation ethanol extracted from leaves starfruit affected the antibacterial activity of Staphylococcus aureus and Pseudomonas aeruginosa . The results showed that the ethanol gel extracted from leaves starfruit (Averrhoa bilimbi Linn.) had the best antibacterial activity, indicated by 65% gel concentration containing the ethanol extracted from leaves starfruit being able to inhibit the growth of Staphylococcus aureus that for 28.62 mm with greater barrier diameter and Pseudomonas aeruginosa for 19 mm. Irritation test to 20 female with age 20 – 30 years old man and woman with put it on the back of hands for 2 hours in 3 days and the result is no irritation indication happend . Gel stability was had test for 4 weeks and nothing change happend